Robust Speech Recognition for Wireless Networks and Mobile Telephony - Haeb-Umbach, Reinhold (Eurospeech)
The increased popularity of mobile telephony introduces both challenges and opportunitites for automatic speech recognition. ASR offers ways to simplify the use of mobile phones, notably in hands- and eyes-busy situations. However, the acoustic environment can be severely degraded and the wireless network may add additional distortions to the speech signal. This paper gives an overview of the sources of degradation and attempts to robust speech recognition for mobile communications. Emphasis is placed on approaches which are suitable for implementation in mobile terminals. Two example applications are described which illustrate the robustness issues and design considerations typical of low-cost noisy speech recognition: voice-dialling in a GSM phone and hands-free digit recognition in the car.